PROBER UTP CABLE SYSTEM (Unshielded twisted PAIR) - Muhammad Azhary; Drs. Lingga Hermanto, MMSi (Jurnal Sistem Komputer, 2008)
In making this writing, the author makes a simple tool with four pieces LED outputdisplay that lights up in sequence.The purpose of this paper is to analyze how the workings of the tool, as well as whatcomponents are used in the manufacture of this tool. In the research / writing, writer usemethod of literature study, namely mengumpukan materials related to this writing ofbooks and test equipment, ie, data collected from the experiment results by using the tooland then analyzed and explained.In this tool use Timer IC that functions as a clock in the display quickly slow theappearance of the display. And is also used IC 4017 (decade counter) that functions as achopper.